2015
DOI: 10.1039/c5sm00973a
|View full text |Cite
|
Sign up to set email alerts
|

Soft microcapsules with highly plastic shells formed by interfacial polyelectrolyte–nanoparticle complexation

Abstract: Composite microcapsules have been aggressively pursued as designed chemical entities for biomedical and other applications. Common preparations rely on multi-step, time consuming processes. Here, we present a single-step approach to fabricate such microcapsules with shells composed of nanoparticle-polyelectrolyte and protein-polyelectrolyte complexes, and demonstrate control of the mechanical and release properties of these constructs. Interfacial polyelectrolyte-nanoparticle and polyelectrolyte-protein comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 28 publications
(46 reference statements)
4
31
0
Order By: Relevance
“…The structure of the interfacial layer, at this magnification, displays wrinkles and sharp cuts, caused by the disruptive sample preparation. The gel resembled a shell-like structure, similar to the microcapsule shells produced by polyelectrolyte-nanoparticle complexation reported by Kaufman et al 42 Homogeneous staining of the interfacial gel (shown in magenta, Fig. 5c) confirmed the presence of embedded oil.…”
Section: Soft Matter Papersupporting
confidence: 81%
“…The structure of the interfacial layer, at this magnification, displays wrinkles and sharp cuts, caused by the disruptive sample preparation. The gel resembled a shell-like structure, similar to the microcapsule shells produced by polyelectrolyte-nanoparticle complexation reported by Kaufman et al 42 Homogeneous staining of the interfacial gel (shown in magenta, Fig. 5c) confirmed the presence of embedded oil.…”
Section: Soft Matter Papersupporting
confidence: 81%
“…Complexation of polymers, surfactants or particles at immiscible liquid interfaces is an increasingly popular technique to produce all-liquid printable, reconfigurable and self-healing membranes, devices and capsules [1][2][3][4][5][6][7][8][9][10][11][12] . While layer-by-layer assembly of components at liquid interfaces enables to obtain good control over membrane thickness and composition [13][14][15] , an easier way to promote interfacial complexation is to dissolve the interacting species within two separate liquid phases, such as oil and water 6,[9][10][11][16][17][18][19][20][21] or two partially-miscible phases 2,5,[22][23][24] . As the components spontaneously diffuse towards the common interface, they selfassemble through non-covalent interactions such as electrostatic ones and form a membrane which grows over time up to micrometric thicknesses 10,11 .…”
mentioning
confidence: 99%
“…water-soluble and oil-soluble PEs to form PE bilayers on waterin-oil droplets during their generation, later expanding the technique to form nanoparticle-PE/protein-PE complexes on the droplets. 24 Zhang et al 25 employed a similar technique using an aqueous two-phase system rather than immiscible fluids. However, while this one-step process is simple and fast for PE bilayer formation, the addition of more layers to form a full PMLC would be non-trivial due to the cumbersome construction of the capillary-in-capillary microfluidic devices.…”
Section: Introductionmentioning
confidence: 99%